Analisis Pengendalian Internal Sistem Informasi Akuntansi terhadap Penerimaan dan Pengeluaran Kas pada Zibaa Kafe: Analysis of Internal Control of Accounting Information Systems on Cash Receipts and Expenditures at Zibaa Cafe - Gita Tri Tanika; Dinar Riftiasari; Achmad Ridwan (CV Warnak Johanna Nusantara, 2025)
Accounting information systems play an important role in managing cash receipts and disbursements to ensure the security and reliability of financial reports. This study aims to analyze the implementation of the accounting information system at PT. Boga Cipta Jasa (Zibaa Kafe) with a focus on internal control and the use of electronic payments. The research method employed is a descriptive qualitative approach through observation, interviews with finance staff and cashiers, and analysis of financial reports for the period January–March 2025. The results show that internal control has not been fully effective due to overlapping functions, lack of verification, and the need for system updates. Although electronic payments have improved accuracy and transparency, further improvements such as clear segregation of duties and regular reconciliations are still required to strengthen the effectiveness and security of the accounting information system.